DEVELOPMENT OF A COMPOSITE ROAD TRAFFIC SAFETY PERFORMANCE INDEX: A BASIS FOR COMPARING TURKISH METROPOLITAN CITIES - Yilmaz, Yunus Emre; Gursoy, Mustafa (YILDIZ TECHNICAL UNIV, 2020)
In this study, we aimed to measure and compare the road traffic safety performance of the current thirty metropolitan cities in Turkey by applying principal components analysis (PCA) with the data from 2016. A total of ten road traffic safety performance indicators from different fields were selected to present the current road traffic safety situation in these cities. The structural and cultural characteristics of the cities were also considered by applying Ward's cluster analysis. Four indicators were used in the cluster analysis, then the cities were ranked according to their road traffic safety performance. The cities with the highest and lowest road traffic safety score were Erzurum and Mugla, respectively. The cities were divided into four classes according to the cluster analysis. The first group includes only Istanbul. The other three groups include seven, ten and twelve cities, respectively.
Keywords: Road safety; traffic safety; principal components analysis; indexes; comparison; Engineering